A rare occurrence of suspected delayed malignant hyperthermia in a young patient undergoing an orthopaedic surgery - Lin, H.J.; Halim, N.A.; Joey, C.; Ming, T.K.; Katiman, F.; Dintan, N.A.; Yeap, Boon Tat (Gazi Universitesi, 2020)
Malignant hyperthermia (MH) is a rare but fatal anaesthetic emergency. It is an autosomal dominant (AD) inherited disorder which is characterized by a hypermetabolic response of an individual upon exposure to a certain type of anaesthesia. We report a rare case of desflurane-induced MH in a Malay descent immediately following an uneventful exposure to sevoflurane. The administration of dantrolene in the immediate management successfully treated the patient.